EFFECTS OF TOP MANAGERS' CABINET APPOINTMENTS ON SHAREHOLDERS' WEALTH. - McGuire, Jean; Schneeweis, Thomas; Naroff, Joel (Academy of Management Journal, 1988)
The article presents information on a study which examined how the appointment of a top executive to a federal government cabinet post affects the firm's stock value. The author describes the use o...